Urban and rural inequality in knowledge, attitude and practice on haze pollution episode in Klang Valley, Malaysia - James N., Vethanayagam; V., How (Malaysian Public Health Physicians' Association, 2017)
Introduction: Transboundary haze occurred was primarily derived from seasonal forest fires which has highly been concerned of the health effect on the local community. As awareness of the source and dangers of smoke haze spread, Malaysian government increasingly came under pressure from the public and civil society at the national, state, and district level to address the haze issues. However, the knowledge, attitude, and practice (KAP) inequalities of urban and rural community could be a barrier in promoting awareness on haze. Objective: To determine the urban and rural inequality in KAP on haze. Methodology: A total of 400 urban and rural residents from Klang Valley was recruited to participate in this study. A validated survey form was used as the study instrument which composed of four parts: (1) Sociodemographic information, (2) Haze knowledge, (3) Attitude (concerns) during haze episodes, (4) Practices (protective behaviors) to prevent against the health effects of haze. Result: There were significant differences of KAP on transboundary haze among urban-rural population. Urban population has higher knowledge and protective behaviors on hazes; however, both the rural-urban residents presented moderate levels of concerns on hazes. Conclusion: It is necessary to provide timely information (knowledge and practices) on haze to rural residents, at the same time, improve the urban residents’ concerns (attitudes) over the haze phenomenon. This will help to raise the overall awareness level to transboundary haze by translating into a state of the resilient community.